Pendampingan Meningkatkan Kompetensi Menulis Artikel Jurnal Mahasiswa Di STIT Al-Urwatul Wutsqo Jombang - Ali Mustofa; Nurul Indana; Ahmad Budiyono; Elysa Nurul Qomaria (An Naf'ah: Jurnal Pengabdian Masyarakat, 2024)
Students' ability to write scientific journals is not only needed to complete coursework or final assignments. Their ability to write scientific journals also has an impact on the fulfilment of university quality standards, because the role of students is very important in achieving these standards. The purpose of the service is to improve students' ability to write scientific journals through mentoring. The purpose of the service is to improve students' ability to write scientific journals through mentoring. In implementing this community service using the Assest Based Community Development (ABCD) method with 5 (five) stages of activity, namely discovery, dream, design, define, and destiny. As a result of community service activities, students can improve their understanding and skills in writing scientific articles, and they can independently publish their work in quality scientific journals. To meet this college standard, it is expected that students contribute to the productivity of research, community service, and publications.